Congenital malformations potentially affecting respiratory function: multidisciplinary approach and follow-up - Fainardi, Valentina; Nicoletti, Laura; Conte, Cristiano; Massa, Serena; Torelli, Lisa; Scarpa, Alberto Attilio; Casolari, Emilio; Esposito, Susanna Maria Roberta; Pisi, Giovanna (Acta Biomedica Atenei Parmensis, 2020)
Background and aim. Congenital malformations such as oesophageal atresia (OA) and tracheoesophageal fistula (TOF), congenital pulmonary airway malformations (CPAMs), congenital diaphragmatic hernia (CDH) and vascular rings (VRs) can affect lung development and respiratory function. This observational study describes our multidisciplinary approach and respiratory follow-up of children with such congenital malformations. Methods. Clinical data of children followed at the Pediatric Respiratory Unit of Parma University Hospital (Italy) between January 2015 and January 2020 were collected. Results. Twenty-three patients with congenital malformation affecting lung development were identified. Almost half of our patients were diagnosed with fetal ultrasound. Children attended the clinic at a mean age of 3 (3.7) years and follow-up visits were scheduled every 6 months average. More than half of our patients were hospitalized for lower respiratory tract infections. Six out of 9 children able to perform spirometry showed anomalies in lung function. Chest physiotherapy was recommended especially in children with OA. Conclusions. Children with congenital malformations affecting lung development are at risk of short and long-term respiratory complications, especially in the first years of life. OA was the malformation more associated to respiratory problems. Multidisciplinary approach and appropriate personalized follow-up are recommended for the best management of these children. Abstract word count: 186